Examining the Role of Health Literacy in Optimizing the Care of Pregnant Women with Diabetes - Yee, Lynn M.; Niznik, Charlotte M.; Simon, Melissa A. (American Journal of Perinatology, 2016)
Diabetes during pregnancy is a substantial and growing public health problem disproportionately affecting women in racial/ethnic minority communities. Health literacy and numeracy are skills needed to function in the health care environment. By definition, health literacy is the degree to which individuals have the capacity to obtain, process, and understand basic health information and services needed to make appropriate health decisions. Health literacy is increasingly recognized as an important mediator of health disparities in the United States, yet it has been rarely studied during pregnancy. Thus, this article aims to describe the problem of inadequate health literacy, outline the relationships between inadequate health literacy and poor health outcomes, and discuss diabetes-specific associations with health literacy. Although literacy has been insufficiently studied during pregnancy, a limited body of work suggests inadequate health literacy may be associated with lesser knowledge and self-care behaviors among pregnant women with diabetes. Health literacy-focused clinical “pearls” for the care of pregnant women with diabetes include: to use multiple educational modalities, to employ teach-back methods, to validate understanding, to provide specific and concrete counseling, and to offer focused, limited messaging. Lastly, future research directions regarding diabetes, health literacy, and pregnancy are addressed.
Keywords: health literacy; health numeracy; gestational diabetes mellitus; type 2 diabetes mellitus; health communication